HEALTH PREGNANCY PROFILE IN SURABAYA CITY - Puji Hastuti (UPT Penerbitan Universitas Jember, 2017)
Background: Pregnancy is a dynamic condition, whereby a situation that is initially normal, can suddenly be at high risk. Risks that occur in pregnant women can be identified by knowing the health status of mothers during pregnancy. This study aims to describe the health status of pregnant women. Methods: The research design used was descriptive observation. The population of all pregnant women who do antenatal care at Puskesmas area of Surabaya city. Sampling using simple random sampling technique, sample are 72 respondents. The variables measured to describe maternal health status include age, education, occupation, history of hypertension, parity and nutritional status. Data collection was done by questionnaire to identify the variable, except nutritional status, the respondents were measured body weight and height, then calculated body mass index. The analysis used descriptive precentage so that known the spread of each variable. Results: The results of this study describe respondent’s age more than 41.7% 20-35 years old. The largest of respondent’s education are SMA, 55.6%. Respondents are as housewives more than 68.1%. The health status of respondents was based on second parity of 38.9%. History of hypertension suffered by respondents, 31.9% suffered from severe hypertension. Maternal nutrition included good category 59.7%. The health status of pregnant women in the city of Surabaya depicted many respondents in the age category not recommended for pregnancy, a history of severe hypertension and poor maternal nutrition causes increased the risk of complications in pregnancy and childbirth. Majority respondents to safe parity of the second and third pregnancies and more dominated by housewives make them potentially seeking antenatal care services. Conclusions: The role of health personnel needs to be improved so that the antenatal care function in an effort to improve the optimal health status of pregnant women. Keywords: Health Status, Pregnant Women, Antenatal care.